Tabungan Perumahan Rakyat (TAPERA) Kajian Kritis dari Konteks Pekerja - Lukmansyah Lukmansyah; M. Asif Nur Fauzi; Yuharso Hadi (AL-UJRAH, 2025)
The Housing Savings Program (Tapera) is an initiative by the Indonesian government aimed at increasing access to homeownership for all segments of society, including informal workers. This study aims to evaluate the perceptions of participants, the transparency of fund management, and the challenges in the implementation of the Tapera program. The research uses a qualitative approach with document study and content analysis to explore relevant literature. The findings reveal that many informal workers face difficulties in participating in this program, especially due to irregular income, as well as a lack of clarity regarding fund management. Moreover, the transparency of Tapera fund management is also an issue that needs more attention to ensure the program operates effectively and meets public expectations. This research suggests adjustments to the contribution policy to make it more flexible, enhanced socialization efforts, and stronger oversight to ensure that Tapera achieves its goal of providing affordable housing.